Behind the success of dominated personal pension plans: sales force and financial literacy factors. (12th October 2020) - Marotta, Giuseppe
Abstract: The revealed preference for dominated insurance-based personal pension plans (PPPs) in Italy is a decade-long puzzle. I surmise that a motivation from the supply side is a sales force factor deriving from the geographical distribution of financial providers, including the countrywide network of the state controlled Post Office. I provide supporting evidence using three biennial waves of the Bank of Italy's survey on household finances from 2010 to 2014. The time interval includes a public pension system reform sharply raising the statutory age retirement, legislated in December 2011 to defuse a sovereign debt crisis. I show that the salience effect on the awareness of the benefits of supplementing lower perspective public pensions with PPPs increased the explanatory power of financial strength indicators. Exploiting a module in the 2010 wave I estimate a surprising decrease in the probability of subscription to PPPs in 2014 associated with the indicator for the highest financial literacy level.